2021
DOI: 10.5109/4480729
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparative of Modified Jatropha Based Nanofluids in Orthogonal Cutting Process

Abstract: As machining operation is getting crucial, thus nanotechnology has been considered in providing more effective performance to reduce friction coefficient and wear protection of both workpiece and tool. This study investigated effect of an inclusion of solid nanoparticle additives such hexagonal boron nitride (hBN), graphene, copper oxide (CuO) at 0.05 wt.% concentration in modified jatropha (MJO) based oil. The performance of nanofluids was evaluated by conducting friction and wear test via four-ball test as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Centre of Gravity of the vehicle is considered for the kerb weight only for dynamics. CG of a vehicle has an effect on Rolling and pitching characteristics 34) . So, CG must be optimum to eliminate excess Roll and pitch which increases instability 35) .…”
Section: Selection Of Parametersmentioning
confidence: 99%
“…Centre of Gravity of the vehicle is considered for the kerb weight only for dynamics. CG of a vehicle has an effect on Rolling and pitching characteristics 34) . So, CG must be optimum to eliminate excess Roll and pitch which increases instability 35) .…”
Section: Selection Of Parametersmentioning
confidence: 99%
“…This double half-h-bridge motor driver allows the control of the motor using PWM signals from a microcontroller. The said driver was chosen for its high current and voltage limits 24) . The motors chosen are capable of drawing about 6 amperes of current at full load at 12 volts; most of the widely available drivers such as L298 drivers are only capable of handling 3 amperes of current at most.…”
Section: Electronicsmentioning
confidence: 99%
“…In addition, activated carbon (AC) is a type of carbonaceous material that has undergone treatment. It possesses a consistent surface shape, notable biocompatibility, favorable mechanical strength, and stability [2,11]. According the preceding investigation conducted by Kaggwa et al, [12], it was observed that the incorporation of activated carbon in nanofluid resulted in a notable augmentation of lubricant viscosity and enhancement of heat transfer efficiency.…”
Section: Introductionmentioning
confidence: 97%
“…Around 85% of MWFs utilized in industrial settings are sourced from petroleum-based oil. This preference is mostly attributed to their commendable lubricating properties, notable stability, and prolonged durability [2].…”
Section: Introductionmentioning
confidence: 99%